1974
DOI: 10.1159/000197556
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Study of Basal Arterial Ammonemia and of Orally-Induced Hyperammonemia in Chronic Portal Systemic Encephalopathy, Treated with Neomycin, Lactulose, and an Association of Neomycin and Lactulose

Abstract: The authors compare the effect of lactulose, neomycin, and an association of these two drugs on fasting arterial blood ammonia levels and the arterial blood ammonia level induced by oral ammonium acetate in nine bed-rested patients with chronic portal systemic encephalopathy. Lactulose and neomycin brought about a similar decrease in blood ammonia level or improvement in ammonia tolerance, but the combination of lactulose and neomycin produced a result significantly greater than either drug alone. The enhanced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

1981
1981
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(5 citation statements)
references
References 7 publications
0
5
0
Order By: Relevance
“…No such antagonism has been observed in clinical studies and combination therapy is the norm in the treatment of hepatic encephalopathy in CLD. The only study of the interaction of these two drugs with regard to serum ammonia is the study of Pirotte et al66 who measured the decline of blood ammonia following administration of lactulose or neomycin individually and in combination. Serial measurements in nine CLD patients with stable blood ammonia elevations showed that lactulose and neomycin used individually resulted in minor reductions in the fasting ammonia concentration of 14% and 18%, respectively.…”
Section: Mechanisms Of Action Of Lactulose and Rifaximinmentioning
confidence: 99%
“…No such antagonism has been observed in clinical studies and combination therapy is the norm in the treatment of hepatic encephalopathy in CLD. The only study of the interaction of these two drugs with regard to serum ammonia is the study of Pirotte et al66 who measured the decline of blood ammonia following administration of lactulose or neomycin individually and in combination. Serial measurements in nine CLD patients with stable blood ammonia elevations showed that lactulose and neomycin used individually resulted in minor reductions in the fasting ammonia concentration of 14% and 18%, respectively.…”
Section: Mechanisms Of Action Of Lactulose and Rifaximinmentioning
confidence: 99%
“…Since 1-3% of the neomycin administered is absorbed, it should be used only during acute episodes of liver failure, at a dosage of 6 g daily. The combined use of lactulose and neomycin has been shown to have an additive effect in reducing gut-derived ammonia production [52,80,84]. The mechanism of this additive effect is not well understood, since one would expect that neomycin might inhibit the effectiveness of lactulose by suppressing bacterial metabolism, which is necessary for its therapeutic effect.…”
Section: Management Of Eneephalopathymentioning
confidence: 99%
“…It has been generally accepted that a combination of lactulose * and neomycin may be used together in the treatment of Portal Systemic Encephalopathy (P.S.E.). A paper by Pirotte et al 1 showed that a combination in low doses of the two compounds together reduced basal arterial ammonia levels more than the two used individually. This finding was somewhat surprising when the mode of action of the two are considered — neomycin being bactericidal to colonic organisms and lactulose requiring these organisms to break it down to organic acids to produce its pH lowering effect — surely antagonistic rather than synergistic.…”
mentioning
confidence: 99%
“…and the former as the drug of choice when there is renal disease, hearing difficulty or when large doses or prolonged use is required. Some patients responding poorly to one preparation do better on the other — more importantly perhaps a percentage of patients find no benefit from the combination although the products might work separately, casting some doubt on the work of Pirotte 1 . Theoretically, neomycin should work in the presence of lactulose although the reverse may not be true.…”
mentioning
confidence: 99%
See 1 more Smart Citation